Penerapan Metode Active Learning Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas Xiia di SMA NU 05 Brangsong Pada Mata Pelajaran PAI - Marjuki, Moch; Afidati, Lulu; Abdul Wakhid, Da’i Muhammad; Husna Dewi, Farihal; Rachmawati, Diana; Mistiyah (LPPM Sekolah Tinggi Islam Kendal, 2025)
This study aims to determine the extent to which the active learning method impacts on increasing student learning motivation in Islamic Religious Education subjects. The subjects of this study involved class XIIA students at SMA NU 05 Brangsong. The purpose of this study was to improve scientific understanding in the field of education, especially in terms of the application of active learning methods. This research was conducted directly in the field using a descriptive qualitative approach. The methods used in data collection included interviews, observation, and documentation. Based on the results of the research data analysis, it can be concluded that efforts to increase learning motivation in Islamic Religious Education subjects for class XIIA students at SMA NU 05 Brangsong through active learning methods include the application of discussion methods. Student learning motivation for Islamic Religious Education subjects consists of two types, namely intrinsic and extrinsic motivation. Intrinsic motivation includes competition among students to be the best in academic terms, the ability to complete and submit assignments on time, and student activeness in the learning process. Meanwhile, extrinsic motivation includes the awarding of grades, the existence of rewards and punishments, the existence of a ranking system in the class, and the application of various learning methods. Keywords: Learning Motivation; Active Learning; PAI Lessons